Separating Xylose from Glucose using Spiral Wound Nanofiltration Membrane: Effect of Cross-flow Parameters on Sugar Rejection - Nurul Fatihah, Mahamad Roli; Wan Mohd Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; A. W., Mohammad (IOP Science, 2017)
A solution model consisted of two different monosaccharides namely xylose and glucose were separated using a pilot scale spiral wound cross-flow system. This system was equipped by a commercial spiral wound nanofiltration (NF) membrane, Desal-5 DK, having a molecular weight cut off (MWCO) of 150-300 g mol-1. The aim of this present work is to investigate the effect of the cross-flow parameters: the trans-membrane pressure (TMP) and the feed concentration (C0) on the xylose separation from glucose. The filtration experiments were carried out in total reflux mode with different feed concentration of 2, 5, and 10 g/L at different TMP of 5,8 and 10 bar. The performances of the NF membrane were evaluated by measuring the permeate flux and sugar rejection for each experiment. All the samples were quantified using a high performance liquid chromatography equipped by a fractive index detector. The experimental results indicated an increase in pressure from 5 to 10 bar which was a notable increase to the permeate fluxes from 2.66 × 10-3 to 4.14 × 10-3L m-2s-1. Meanwhile, an increase in the C0 increases the xylose rejection. At TMP of 10 bar and C0 of 5 g/L, the observed xylose rejection and glucose rejection were measured at 67.19% and 91.82%, respectively. The lower rejection in xylose than glucose suggested that larger glucose molecule were not able to easily pass through the membrane compared to the smaller xylose molecule. The results of this phenomena proved that NF with spiral wound configuration has the potential to separate xylose from glucose, which is valuable to the purification of xylose in xylose production as an alternative to chromatographic processes.